Relationships between couple collaboration, well-being, and psychological health of infertile couples undergoing assisted reproductive treatment - Marzie Reisi; Ashraf Kazemi; Shokofeh Maleki; Zahra Sohrabi (BMC, 2024)
Abstract Background Social problems related to infertility are associated with a significant psychological burden for the involved couple. Previous studies have shown the positive effects of couple interactions on the psychological health of these couples; however, the specific conditions of participating in assisted reproductive treatments (ART) might influence the effect of couple collaboration. Therefore, the present study aimed to evaluate the relationship between couple collaboration, well-being during infertility, and the psychological indicators of infertile couples undergoing fertility treatment. Methods This cross-sectional study was conducted on 200 ART volunteer couples. Couple collaboration and well-being during infertility were evaluated using a validated researcher-made questionnaire, and the level of depression, anxiety, and stress was evaluated using the DASS-21 questionnaire in both couples. Statistical analysis was performed using the plug-in application PROCESS macro for SPSS and AMOS software. Results The results showed that couple collaboration was correlated with the level of depression, anxiety, and stress. Moreover, depression, anxiety, and stress levels were correlated with well-being during infertility. The direct and indirect effect of couple collaboration on the depression level was significant; however, the direct effect of couple collaboration on the level of anxiety and stress was not significant, and the effect of couple collaboration on these indicators was mediated by well-being during infertility. The fit index of the equation modelling showed a good fit of the relationship path between the variables of couple collaboration, well-being during infertility, and psychological indicators (CMIN = 4.196, p = 0.260). Conclusion The results of this study show that the specific conditions of participating in ART may affect the direct effects of couple interaction on an infertile couple's levels of anxiety and stress. These results suggest that in order to develop mental health programs for infertile couples, strategies based on couple collaboration that are associated with higher well-being during infertility should be developed and presented.